Aspects of pruning and manipulation of regrowth in citrus - Punt, Heinrich F.(Heinrich Friedrich) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1998.